The Relevance Between Pesantren's Character Education and Ismail Raji Faruqi's Thought - Abdullah, Moh.; Abu Bakar, Yunus; Rachman Assegaf, Abd. (The Institute of Research and Service Community IPMAFA Pati, 2024)
This article reviews the relevance of Ismail Raji al-Faruqi's views on monotheism education and character education, focusing primarily on moral and religious education in Islamic boarding school environments in Indonesia. Monotheism education, a central concept in Ismail Raji al-Faruqi's thinking, is considered a crucial foundation in the development of science. The method used is library research, which collects and analyzes data from various sources such as books, journals, and related research. This research produces findings that al-Faruqi's concept of monotheism education is substantively relevant to character education, especially in the context of developing moral and religious character in Islamic boarding school environments. Al-Faruqi's contribution to enriching character education in Pesantren through a monotheistic approach helps ensure that Islamic values ​​and holistic personal development become the main focus, producing individuals with good morals committed to developing knowledge.